Physical, mechanical and gamma-ray shielding properties of highly transparent ZnO-MoO3-TeO2 glasses - Ersundu, M. Celikbilek; Ersundu, A. E.; Gedikoglu, N.; Sakar, E.; Buyukyildiz, M.; Kurudirek, M. (ELSEVIER, 2019)
Physical, mechanical and radiation shielding properties of ZnO-MoO3-TeO2 glasses were studied. Density, molar volume, oxygen molar volume, oxygen packing density were evaluated for the interpretation of physical properties. Mechanical properties were determined through Vickers hardness measurements. The shielding estimation was accomplished by studying linear attenuation coefficient (LAC mu), mass attenuation coefficient (MAC), effective atomic number (Z(eff)), effective electron density (N-eff), mean free path (mfp), exposure buildup factor (EBF) and energy absorption buildup factor (EABF). The glasses were irradiated by Ba-133 radioactive source emitting gamma rays in the range of 79.61 keV to 383.80 key to determine LACs and MACs. mfp values were calculated for present glasses and compared with various concretes and a commercial window glass in energy region 81-384 key. The glass structure became stronger and mechanical properties showed an increment with increasing MoO3 content. Synthesized glasses have lower mfp values indicating better shielding properties than concretes and window glass.
Keywords: Shielding glasses; Density; Hardness; Mean free path; Exposure buildup factor; Energy absorption buildup factor; METAL OXIDE GLASSES; STRUCTURAL-PROPERTIES; PARAMETERS; Materials Science